Urgensi Evaluasi Pembelajaran Untuk Meningkatkan Karakter Santri di TPA Al - Munawaroh - Azizah Adelia Rahma; Eka Widyanti; Difana Leli Anggraini; Siti Nurfaizah (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
The aim of this research is to describe and analyze learning evaluations which aim to enable educators to measure student assessments. This research method uses qualitative with descriptive research type. Primary data sources are TPA teachers and secondary data from relevant journals and books. Data collection technique; observation, interviews and documentation. The results of the research are by providing an assessment rubric to teachers so that the results of the assessment are accurate. By providing ice breaking to the students there it also makes learning fun and not boring. And also show a video of the practice of good attitudes from Rasulullah Shallahu 'alaihi Wassalam. As a result, students' characteristics can improve compared to before because of well-structured learning evaluations.